1999
DOI: 10.1300/j074v11n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Early Childbearing Patterns and Women's Labor Force Behavior in Later Life

Abstract: The purpose of this research is to evaluate the consequences of early childbearing decisions for women's labor force activity in later life. Within a life course framework, women's early childbearing activities may be linked to later life decisions. Women between ages 55 and 64 are evaluated from the 1984 Survey of Income and Program Participation. Two measures of early family roles are considered: total fertility (number of children ever born) and timing of first-birth (childless, prior to age 30, and 30+). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 18 publications
6
62
1
1
Order By: Relevance
“…Some qualitative studies have paid attention to the role of family histories for understanding women's retirement decisions and outcomes (e.g., August and Quintero 2001;Everingham et al 2007). Quantitative studies have generally focused on either early life family experiences (Hank 2004;Hank and Korbmacher 2013;Pienta 1999) or the late career family context (Brown and Warner 2008;Choi 2002;Szinovacz et al 2001) for explaining women's late career labor market behaviors. Very few studies have captured fertility or marital trajectories in more detail (e.g., Finch 2014).…”
Section: Issues By Examining the Following Research Question: To Whamentioning
confidence: 99%
See 1 more Smart Citation
“…Some qualitative studies have paid attention to the role of family histories for understanding women's retirement decisions and outcomes (e.g., August and Quintero 2001;Everingham et al 2007). Quantitative studies have generally focused on either early life family experiences (Hank 2004;Hank and Korbmacher 2013;Pienta 1999) or the late career family context (Brown and Warner 2008;Choi 2002;Szinovacz et al 2001) for explaining women's late career labor market behaviors. Very few studies have captured fertility or marital trajectories in more detail (e.g., Finch 2014).…”
Section: Issues By Examining the Following Research Question: To Whamentioning
confidence: 99%
“…Educational investments have been found to be an important predictor of access to jobs involving substantively complex or challenging work (Hyllegard and Lavin 1992), which in turn have been found to be associated with later (intended) retirement (Hayward et al 1998;Hayward et al 1989;Henkens 1999). Consequently, it can be hypothesized that women who had their first child relatively late (intend to) retire later than women who had their first child relatively early (Hypothesis 1) because of their more beneficial preretirement work situation and stronger labor force attachment (Pienta 1999).…”
Section: Childbearing Histories and Women's Retirement Timingmentioning
confidence: 99%
“…Research findings regarding fertility histories and retirement are rather mixed though, even when focusing on women. Whereas some studies have shown that the number of children is not clearly associated with labor force exit among women (Pienta 1999, Finch 2014, other studies have shown that having (more) children is associated with later retirement (Chung 2010, Hank 2004, O'Rand and Henretta 1982. A recent study by Hank and Korbmacher (2013) based on the SHARELIFE data has revealed that the impact of the number of children on women's retirement timing differs across birth cohorts.…”
Section: Family Histories and Retirement Timingmentioning
confidence: 99%
“…Also with respect to the timing of having a first child, conclusions vary across studies. Some authors conclude that the timing of first birth does not seem to matter much for explaining late-career labor force exit (Finch 2014, Hank andKorbmacher 2013), others conclude that having a first child relatively early is related to a lower likelihood of self-defined retirement and labor force exit (Chung 2010), and yet others find that a relatively late transition into motherhood is associated with rejection of the retiree identity (Szinovacz and DeViney 1999), and later labor force exit (Hank 2004, Pienta 1999. Damman, Henkens, and Kalmijn (2014) showed that women who transitioned into motherhood relatively late and still have children living at home during preretirement years intend to retire relatively late, but do not actually retire later.…”
Section: Family Histories and Retirement Timingmentioning
confidence: 99%
See 1 more Smart Citation